Aging and scleroderma. (April 2011) - Manno, Rebecca L; Hummers, Laura K
Although rare in the general population, geriatricians and general practitioners should be aware of the clinical manifestations of systemic sclerosis (SSc) as it can present at an older age and may have unique patterns of organ involvement. Furthermore, recent important advances in treatment have improved survival among SSc patients resulting in a distinct population aging with SSc. Symptoms of SSc overlap frequently with those of the aging population (such as gastroesophageal reflux disease and cold sensitivity), however, specific features, such as the new onset of Raynaud phenomenon or the new onset of swelling of the hands and feet, should prompt an evaluation for SSc. Elderly-onset SSc patients may have higher rates of specific organ manifestations (such as pulmonary hypertension) but can present with the whole spectrum of SSc. The diagnosis and care of elderly patients with SSc present unique and challenging issues best approached by a multidisciplinary team focusing on each SSc-specific organ system.